ISLAMIC EDUCATION LEADERSHIP IN CONFLICT STATE: CASE STUDY IN SOUTHERN THAILAND - Lailiyatul Azizah; Moch. Khafidz Fuad Raya (Universitas Islam Negeri (UIN) Mataram, 2021)
This study aims to explore the practice of Islamic education leadership in the conflict state, in Pattani Southern Thailand, a region where the conflict is prolonged until the decades are between the Malay Muslim minority with the Thai government that is Buddhist. Using a qualitative approach with the method of case study, this study focused on Madrasah Pattani, with the head of madrasa, one teacher, and three alumni as informants. Interviews were conducted with FGD to find out the extent of leadership in Pattani Madrasas during the conflict. The results were found that in hard conditions, the madrasa could develop a strong madrasa vision by adopting a modern curriculum and integrate it with the Islamic curriculum of Islam. Although this method has been opposed to the entry of Buddhist teachers, the head of madrasah neutralise by making several activities to create social cohesion and build cooperation with universities abroad. Leadership mode is rare and difficult to implement in areas that are being hit by an ethno-political conflict on behalf of religion.